Travel Lifestyle and Travelling Among Millennials to Domestic Destination (Empirical Study in Pontianak City) - admin, Yahya Al Fatih B1024151016 (Jurnal Manajemen Update, 2020)
The purpose of this paper is to investigate the impact of Lifestyle among millennials on their attitude toward travelling activities. In this period, traveling has become one of the activities most in demand by the community, many people try to get rid of boredom by switching to traveling, and not a few people who think traveling has become a hobby and lifestyle, because traveling itself has become a trending topic in the community. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research is Millennials in Pontianak City who are between 20 - 39 years old. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: The Lifestyle have effect to Tours Preferences, H2 : The Travel Motivation have effect to Tours Preferences, H3: The Lifestyle have effect to Consumer Intention to Travelling, H4: : The Travel Motivation have effect to Consumer Intention to Travelling, H5: The Tours Preferences have effect to Consumer Intention to Travelling. The result of this research shows that all the Hypothesis are accepted.Â Keyword: Lifestyle, Travel Motivation, Tour Preferences, Travelling, Millennials